Vitamin B(12) levels in erythrocytes in normal subjects and in pernicious anaemia - Harrison, R. J. (1970)
A reliable method is described for the assay of vitamin B(12) activity in erythrocytes using Lactobacillus leichmannii. The results are shown for age, sex, and blood group in normal subjects, and before, during, and after therapy in vitamin B(12) deficiency anaemia. The normal range is 85-225 pg/ml (mean = 155 ± 35 pg/ml). Raised levels were found in the newborn, and subnormal levels in subjects aged 70 years and over and in males aged 10 to 19 years. There were no differences in erythrocyte vitamin B(12) levels between the ABO or Rhesus blood groups. In pernicious anaemia low levels are found before treatment (mean = 91 pg/ml), followed by a rapid rise during vitamin B(12) therapy (mean peak = 482 pg/ml), and falling more slowly towards normal after the initial haematological response.